Persepsi dan Minat Penggunaan Aplikasi Paylater - Lailatul Rofiah; Maria Augustine Graciafernandy (Jurnal Ilmiah Aset, 2023)
The research was conducted with the aim of testing the influence of perceived ease of use, perceived usefulness, and perceived security to intention to use the paylater aplication. This is because the number of E-commerce users in Indonesia continues to increase every year in 2017 - 2020 and the number of paylater payment system users has also increased from the previous year. This study uses a quantitative approach or method, the population used is the user of the paylater aplication. The sample used in this study was 108 respondents taken by purposive sample method. Data obtained by using a quesionnaire using a likert scale and data analysis used using multiple linear regression analysis. The results of this study indicate that perceived ease of use has a negative and not significant effect on the intention to use the paylater aplication. Perceived usefulness has a positive and significant effect on the intention to use paylater aplication, and perceived security has a positive and significant effect to intention to use paylater aplication.